PENERAPAN MODEL COOPERATIVE SCRIPT DALAM PEMBELAJARAN MENULIS STRUKTUR SURAT RESMI DI KELAS VII SMP USWATUN HASANAH 2022/2023 - Efendi, Irfan; Apriyanto , Ade; Yazid, Muhammad (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This study investigates the effectiveness of the cooperative script method in improving the ability of class VII students at Uswatun Hasanah Middle School to write formal letters. The research involved 15 students from the control class (VII A) and 16 students from the experimental class (VII B). Motivated by the observed challenges in analyzing official letter structures and linguistic conventions, the research aimed to address two key questions: 1) Is the cooperative script method effective for teaching formal letter writing to class VII students at Uswatun Hasanah Middle School?; and 2) What is the learning activity like when using the cooperative script method for writing formal letters in class VII at Uswatun Hasanah Middle School? Employing an experimental study design, data were collected through observations and pretest-posttest assessments. Statistical analysis indicated a significant improvement in the experimental group's performance (tcount = 2.960), supporting the conclusion that the cooperative script method effectively enhances formal letter writing skills among class VII students at Uswatun Hasanah Middle School.